Some aspects of the Ukrainian fiscal policy in the context of decentralization: the revenue of local budgets - Ostrovetskyy, V. (Економічний вісник Донбасу, 2016)
As a result of the macroeconomic assessment of fiscal policy found an inverse relationship between the level of tax burden on economic growth and the physical GDP. It suggested several ways of reforming the tax legislation, which contribute to economic growth on the basis of the balance of interests of the Government, business and local government.